2018
DOI: 10.1126/scisignal.aan1210
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4-phosphate is a major source of GPCR-stimulated phosphoinositide production

Abstract: Phospholipase C (PLC) enzymes hydrolyze the plasma membrane (PM) lipid phosphatidylinositol 4,5-bisphosphate (PI4,5P) to generate the second messengers inositol trisphosphate (IP) and diacylglycerol (DAG) in response to receptor activation in almost all mammalian cells. We previously found that stimulation of G protein-coupled receptors (GPCRs) in cardiac cells leads to the PLC-dependent hydrolysis of phosphatidylinositol 4-phosphate (PI4P) at the Golgi, a process required for the activation of nuclear protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 35 publications
2
34
0
1
Order By: Relevance
“…As above, neurons were studied under whole-cell brain-slice voltage-clamp conditions. From the robust literature documenting M 1 R-mediated depression of I M in multiple types of peripheral neurons and the known increase in neuronal excitability in hippocampus and other brain regions resulting from mAChR stimulation (Bymaster et al, 2003;Shen et al, 2005;Sheffler et al, 2009;Chiang et al, 2010), we expected parallel results from DGGCs and CA1 neurons. However, this was not the case.…”
Section: G Q/11 -Coupled Muscarinic Receptor Stimulation Enhances I Mmentioning
confidence: 94%
See 2 more Smart Citations
“…As above, neurons were studied under whole-cell brain-slice voltage-clamp conditions. From the robust literature documenting M 1 R-mediated depression of I M in multiple types of peripheral neurons and the known increase in neuronal excitability in hippocampus and other brain regions resulting from mAChR stimulation (Bymaster et al, 2003;Shen et al, 2005;Sheffler et al, 2009;Chiang et al, 2010), we expected parallel results from DGGCs and CA1 neurons. However, this was not the case.…”
Section: G Q/11 -Coupled Muscarinic Receptor Stimulation Enhances I Mmentioning
confidence: 94%
“…In a variety of tissues, stimulation of G q/11 -coupled receptors stimulates PIP 2 synthesis concurrently with PLC hydrolysis, driven by rises in [Ca 2ϩ ] i (Lassing and Lindberg, 1990; Racaud-Sultan et al, 1993; Loew, 2007). Both physiological data in cerebellar neurons and biophysical model-ing (Finch and Augustine, 1998;Takechi et al, 1998;Brown et al, 2008) indicate that stimulation of G q/11 -coupled receptors must increase PIP 2 abundance in dendrite spine membrane by 2.5-fold to account for accumulation of local intracellular IP 3 . In sympathetic neurons, subcellular microdomain organization precludes M 1 R stimulation from inducing IP 3 -mediated [Ca 2ϩ ] i rises, allowing substantial PIP 2 depletion, whereas bradykinin B 2 R stimulation, for example, provokes sufficient rises in [Ca 2ϩ ] i and stimulation of PIP 2 synthesis to compensate for any decrease in PIP 2 abundance by PLC hydrolysis (Falkenburger et al, 2010).…”
Section: Pip 2 Synthesis Is Strongly Enhanced By Stimulation Of G Q/1mentioning
confidence: 99%
See 1 more Smart Citation
“…It has a high catalytic activity to cleave the substrate phosphatidylinositol 4,5-bisphosphate (PIP2) into the second messengers, diacylglycerol (DAG) and inositol 1,4,5-trisphosphate (IP3). It has been suggested that PLC-βdependent IP1 accumulation also includes contributions from the IP2 formed by direct hydrolysis of PI4P, instead of IP2 formed by the dephosphorylation of IP3 formed by hydrolysis of PIP2 45 . Since this novel pathway does not depend on PIP2, which is predominantly found at the plasma membrane, the PI4P-dependent IP1 accumulation could have a substantial contribution to PLC-β signaling from the endosomal compartment.…”
Section: [Scheme 1]mentioning
confidence: 99%
“…These proteins hydrolyze phosphatidylinositol-4,5-bisphosphate (PIP2) at the plasma membrane, producing the second messengers inositol-1,4,5-triphosphate (IP3) and diacylglycerol (DAG), which increase Ca 2+ in the cytoplasm and activate protein kinase C (PKC), respectively. However, some PLC subfamilies, such as PLCe, also hydrolyze other phosphatidylinositol phosphate (PIP) species at internal membranes (3)(4)(5)(6). Thus, PLC enzymes regulate multiple pathways from different subcellular locations (1,2).…”
Section: Introductionmentioning
confidence: 99%